INFANTS FEEDING AND WEANING PRACTICES AMONG MOTHERS IN NORTHERN KORDOFAN STATE, SUDAN - Mohammed, Somiya Gutbi Salim (European Scientific Journal, ESJ, 2014)
Background: Several studies undertaken in both developed and developing countries to identify an infant’s feeding and weaning practices among mothers. In Sudan, however, few data available concerning this type of studies,particularly in Northern Kordofan. Objectives: This study aimed to identify the infants feeding and weaning practices among mothers of children from Zero to24 months of age in three towns (Bara, Al-Rahad, and Al-Nuhoud)in North Kordofan State. Methods:Data was collected through personal interview and specifically designed questionnaire. Study sample consisted of 250 families. Results:Breast feeding was initiated immediately after birth within 83.6 % of mothers. Almost half of the mothers (55.2%) stopped breastfeeding when the child was 24 months old. The age of termination of breast feeding was significantly influenced by the education of the mothers. (p value=0.01). It was observed that only 6.8% of the mothers in the present study practiced exclusive breastfeeding. The majority of the mothers (91.6%)introduced complementary foods before six months of age while only 8.4 % started given foods at six month and over. Significant association was found between education and the age of introduction of complementary foods (p value = 0.002). Almost half of the mothers (52%) abruptly weaned their children while only 11.6% gradually weaned their children and some foods were proscribed from the chidden diet. This study concludes thatboth positive and negative infants feeding practices among mothers towards their children and recommended acceptable strategies to promote infant feeding to reduce infant mortality and morbidity rate in Sudan.